Nutrition Transition and Agricultural Transformation: A Preston Curve Approach. - Masters, William A. (Tufts University. Tisch Library., 2017)
This presentation covers a range of topics related to agriculture, nutrition, and food supplies, including: diabetes, obesity, diarrhea, stunting, wasting, and formal policies on food prices.; Keywords: Agriculture, Nutrition, Food Supply, diabetes, diarrheal disease, adult obesity, child stunting , child wasting, diet quality, agricultural transformation , food price policy, Tufts University.; NIL Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy